2021
DOI: 10.1155/2021/6515792
|View full text |Cite
|
Sign up to set email alerts
|

Application and Research of the Intelligent Management System Based on Internet of Things Technology in the Era of Big Data

Abstract: With the in-depth application of the Internet of Things, many emerging technologies are changing the global industry landscape on an unprecedented scale. At the same time, they also provide an opportunity for the development of intelligent management to break through the bottleneck. The proposal and evolution of the concept of intelligent management makes the development of management technology more advanced. Therefore, the introduction of the Internet of Things technology into intelligent management has very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 21 publications
0
57
0
Order By: Relevance
“…The proposed method performs well in most cases, reaching 90.8% for coarse classification, 76.6% for medium classification, and 73.4% for fine classification. GKSC has better performance than KNN, and in medium classification experiments, the performance of GKSC is similar to KNN [24]. However, in most cases, the performance of both KNN and GKSC degrades as the classification accuracy increases.…”
Section: Resultsmentioning
confidence: 85%
“…The proposed method performs well in most cases, reaching 90.8% for coarse classification, 76.6% for medium classification, and 73.4% for fine classification. GKSC has better performance than KNN, and in medium classification experiments, the performance of GKSC is similar to KNN [24]. However, in most cases, the performance of both KNN and GKSC degrades as the classification accuracy increases.…”
Section: Resultsmentioning
confidence: 85%
“…It is reported that there are currently about 300 million hypertensive patients in 2020 in China and this number is still growing. Chronic diseases have become the number one killer of urban populations [ 1 ]. On the other hand, due to the uneven distribution of medical resources, there are urban-rural differences and regional differences.…”
Section: Introductionmentioning
confidence: 99%
“…Customer preferences, market orientation, and policy changes are changing all the time, and even the entire ecological structure of the enterprise will change. If incumbent companies are greedy for the existing success and inherent stable model, they will be overtaken by latecomers and lose their former glory [20].…”
Section: Introductionmentioning
confidence: 99%